THE EFFECTIVENESS OF POPULATION ADMINISTRATIVE DOCUMENT SERVICE DELIVERY (FAMILY CARDS AND BIRTH CERTIFICATES) IN THE GORONTALO CITY DEPARTMENT OF POPULATION AND CIVIL REGISTRATION - Husain, Odi Prawira; Abdussamad, Zuchri; Sulila, Ismet (Public Policy Journal, 2021)
This research aims to analyze and describe the effectiveness of family card and birth certificate service delivery in the Gorontalo City Department of Population and Civil Registration, as well as the supporting and inhibiting factors It used a qualitative descriptive approach. Research data sources were primary and secondary and data collection methods were observation, interview, and documentation. The data analysis technique applied was Miles and Huberman’s interactive model. Research findings attest to the effectiveness of population administrative document service delivery, which in this case, the documents were family cards and birth certificates, based on the effectiveness scale by JP. Campbell, was that (1) The entire program was considered effective, based on all services delivered and registered in SIAK, (2) A target success was ineffective as the achievement of family cards did not meet the target predetermined, (3) In regard to public satisfaction, most communities gave positive responses but with several notes to elevate service quality, (4) Input and output levels by service delivery procedures, service delivery schedule, service delivery cost, facilities and infrastructures, and apparatuses’ competencies were ineffective, and (5) The ultimate goal was to achieve all service delivery aspects, specifically in relation to family cards and birth certificates. Proponent factors of the effectiveness of birth certificate service delivery were both internal and external, breeding a high achievement of birth certificates. Factors inhibiting the effectiveness of family card delivery services were internal, i.e., the condition of the Department itself, and external, i.e., public awareness of and concerns on population documents, especially family cards.